Adsorption method for nitrogen-oxygen separation, lithium type X molecular sieve adsorbent and preparation thereof
By mixing NAX molecular sieves with adhesives to prepare small balls, potassium, ammonium, and lithium ion exchange are performed, combined with the lithium ion exchange of double -phase reverse flow, solving the problem of cumbersome and nitrogen oxygen separation coefficients of the existing LIX molecular screening system and the lack of nitrogen oxygen separation coefficients , Achieve higher nitrogen oxygen separation efficiency.
Patent Information
- Application Number
- CN202310922937.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-07-26
AI Technical Summary
In the existing nitrogen-oxygen separation technology, the preparation process of LiX molecular sieve is complicated, the equipment requirements are high, and the molecular sieve is easily lost when transferred between steps, resulting in a low nitrogen-oxygen separation coefficient.
Use NAX molecular sieves and binders to prepare small balls. After drying and roasting, potassium ion exchange and ammonium ion exchange are performed in order, and lithium ion exchange with double -phase reverse flow is obtained to obtain a lithium X -molecular sieve adsorption agent.
It improves the completeness and adsorption capacity of the molecular sieve, and increases the nitrogen oxygen separation coefficient, such as 6.04-6.14, which is better than the traditional method.
Smart Images

Figure FT_1 
Figure BDA0004359177330000081 
Figure BDA0004359177330000091
Abstract
Description
Technical Field
[0001] The present invention relates to an adsorption method for separating nitrogen and oxygen, an adsorbent and a preparation method thereof. More specifically, the present invention relates to an adsorption method for separating nitrogen and oxygen in the air, a lithium-type X molecular sieve adsorbent and a preparation method thereof. Background Art
[0002] Zeolite molecular sieve is an excellent adsorbent with strong adsorption capacity for polar small molecules and selective adsorption for molecules with different critical diameters, shapes, unsaturation, etc. Therefore, it is widely used in many separation fields, especially in the gas separation industry. Air separation oxygen production uses specific zeolite molecular sieves to separate nitrogen and oxygen by adsorbing nitrogen or oxygen in the air. LiX molecular sieve is used in industrial air separation units due to its excellent nitrogen adsorption characteristics.
[0003] Industrial nitrogen oxide adsorbent is obtained by exchanging X molecular sieve with cations to obtain LiX molecular sieve, then mixing it with clay in a certain proportion, and then rolling, drying and roasting to obtain adsorbent balls. The exchange degree and adsorption capacity of Li ions are important indicators for evaluating adsorbents. Higher exchange degree and adsorption capacity are conducive to obtaining higher nitrogen oxide separation coefficients.
[0004] CN101289196A discloses a method for preparing LiLSX molecular sieve, including preparing LSX zeolite, exchanging LSX into KLSX, using K2SO4 solution, adjusting the pH value to 8.5 with KOH solution, multiple replacement methods, each replacement time is 2 minutes, the solution temperature is about 80°C, and the exchange solution after the first few exchanges is used for the next batch of K + Exchange process; then adopt and K + The solution was replaced by NH4LSX in a similar way, with a pH value of 8.5; then, LiOH solution was used at 50 °C to carry out Li + The ions are exchanged into LiLSX, and air is introduced to discharge NH3. Finally, the ions are washed and dried to obtain the finished product, and the Li ion exchange degree is greater than 95%. This method has many steps, a long time and a complicated process, and the molecular sieve is easily lost when it is transferred between the steps.
[0005] CN102502694A discloses a method for preparing a LiLSX molecular sieve. In this method, the X molecular sieve raw powder is first exchanged with an ammonium salt, and then a lithium salt solution is impregnated into the molecular sieve by an impregnation method, and then dried and calcined to obtain a Li-modified X molecular sieve. This method improves the utilization rate of Li ions, but cannot ensure that all Li ions are exchanged to ion sites, and some free lithium salts will be present.
[0006] CN114408941A discloses a method for preparing LiX molecular sieve, which comprises: mixing X molecular sieve with Li + Mix the recovered liquid with Li + The exchange liquid is used to perform countercurrent exchange treatment on the pre-exchanged X molecular sieve under vacuum conditions for 9 to 15 times, and the filtrate produced after each countercurrent exchange treatment is recovered as a Li-containing + The exchange liquid is subjected to the next countercurrent exchange treatment, and the filtrate produced after the last countercurrent exchange treatment is recovered as the recovered liquid; the X molecular sieve obtained after the countercurrent exchange treatment is dried. This method has high requirements on equipment and the process is cumbersome. Summary of the invention
[0007] The inventors found that compared with LiX molecular sieves, NaX molecular sieves have a more stable lattice at high temperatures. After high-temperature calcination, the lattice collapse and damage of NaX molecular sieves are less, and the integrity is higher. In the present invention, when the NaX molecular sieve is first mixed with a binder to prepare a small ball, after drying and calcining, the small ball is sequentially subjected to potassium ion exchange, ammonium ion exchange and lithium ion exchange in a two-phase countercurrent to obtain a lithium-type X molecular sieve adsorbent. Compared with the lithium-type molecular sieve first obtained and then mixed with a binder and dried and calcined, the obtained lithium-type X molecular sieve adsorbent has a high molecular sieve lattice integrity and a large adsorption capacity. When applied to the adsorption method for nitrogen and oxygen separation, its nitrogen and oxygen separation coefficient is higher.
[0008] Therefore, one of the objects of the present invention is to provide an adsorption method for nitrogen-oxygen separation, which has a better nitrogen-oxygen separation coefficient; the second object of the present invention is to provide a preparation method of a lithium-type X molecular sieve adsorbent in the adsorption method for nitrogen-oxygen separation; the third object is to provide a lithium-type X molecular sieve adsorbent obtained by the preparation method.
[0009] In order to achieve one of the purposes of the present invention, the present invention provides an adsorption method for separating nitrogen and oxygen, which uses a lithium-type X molecular sieve adsorbent to separate nitrogen and oxygen from air, characterized in that the lithium-type X molecular sieve adsorbent is prepared by a method comprising the following steps:
[0010] (1) NaX molecular sieve and binder are uniformly mixed in a mass ratio of 80-95:5-20, and the mixture is formed into balls by rolling, the balls are dried at 60-110° C., and then calcined at 500-700° C. to obtain calcined balls;
[0011] (2) subjecting the calcined pellets of step (1) to ion exchange with a soluble potassium salt solution to obtain potassium-type pellets;
[0012] (3) exchanging the potassium-type beads in step (2) with a soluble ammonium salt solution to obtain ammonium-type beads;
[0013] (4) exchanging ions of the ammonium beads in step (3) with a soluble lithium salt solution in a two-phase countercurrent exchange manner, draining and in-situ drying are performed in sequence after the exchange is completed to obtain the lithium-type X molecular sieve adsorbent; the two-phase countercurrent exchange is performed in a columnar container, air is introduced into the bottom of the container, and the air and the soluble lithium salt solution pass through in countercurrent.
[0014] In order to achieve the second object of the present invention, the present invention provides a method for preparing a lithium-type X molecular sieve adsorbent, characterized in that the preparation method comprises the following steps:
[0015] (a) mixing NaX molecular sieve and binder in a mass ratio of 80-95:5-20, forming the balls by rolling, drying the balls at 60-110° C., and calcining the balls at 500-700° C. to obtain calcined balls;
[0016] (b) subjecting the calcined pellets of step (1) to ion exchange with a soluble potassium salt solution to obtain potassium-type pellets;
[0017] (c) exchanging the potassium-type beads in step (2) with a soluble ammonium salt to obtain ammonium-type beads;
[0018] (d) exchanging ions of the ammonium beads in step (3) with a soluble lithium salt solution in a two-phase countercurrent exchange manner, draining and in-situ drying are performed in sequence after the exchange is completed to obtain the lithium-type X molecular sieve adsorbent; the two-phase countercurrent exchange is performed in a columnar container, air is introduced into the bottom of the container, and the air and the soluble lithium salt solution pass through in countercurrent.
[0019] In order to achieve the third object of the present invention, the present invention further provides a lithium type X molecular sieve adsorbent prepared by the preparation method of the above lithium type X molecular sieve adsorbent.
[0020] The adsorption method for separating nitrogen and oxygen provided by the present invention adopts a lithium-type X molecular sieve adsorbent, wherein a NaX molecular sieve is first mixed with a binder to prepare a small ball, dried and calcined, and then sequentially subjected to the process steps of potassium ion exchange, ammonium ion exchange and lithium ion exchange in a two-phase countercurrent manner. The method has a high nitrogen and oxygen separation coefficient, for example, up to 6.04-6.14, while the comparative lithium-type X molecular sieve adsorbent obtained by conventional kettle lithium exchange or the comparative lithium-type X molecular sieve adsorbent obtained by first exchanging the NaX molecular sieve with the LiX molecular sieve and then mixing with the binder to dry and calcine the nitrogen and oxygen separation coefficients are 6.02 and 6.01 respectively.
[0021] The preparation method of the lithium type X molecular sieve adsorbent provided by the invention also has the characteristics of high lithium ion exchange degree and lithium utilization rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1It is a countercurrent column ion exchange device. DETAILED DESCRIPTION
[0023] A nitrogen-oxygen separation adsorption method is to separate nitrogen and oxygen from air using a lithium-type X molecular sieve adsorbent, characterized in that the lithium-type X molecular sieve adsorbent is prepared by a method comprising the following steps:
[0024] (1) NaX molecular sieve and binder are uniformly mixed in a mass ratio of 80-95:5-20, and the mixture is formed into balls by rolling, the balls are dried at 60-110° C., and then calcined at 500-700° C. to obtain calcined balls;
[0025] (2) subjecting the calcined pellets of step (1) to ion exchange with a soluble potassium salt solution to obtain potassium-type pellets;
[0026] (3) exchanging the potassium-type beads in step (2) with a soluble ammonium salt to obtain ammonium-type beads;
[0027] (4) exchanging ions of the ammonium beads in step (3) with a soluble lithium salt solution in a two-phase countercurrent exchange manner, draining and in-situ drying are performed in sequence after the exchange is completed to obtain the lithium-type X molecular sieve adsorbent; the two-phase countercurrent exchange is performed in a columnar container, air is introduced into the bottom of the container, and the air and the soluble lithium salt solution pass through in countercurrent.
[0028] In the adsorption method of the present invention, the SiO2 / Al2O3 molar ratio of the NaX molecular sieve in step (1) is 2.0 to 2.15. The binder is at least one of palygorskite, kaolinite, dickite, perlite, refractory stone and halloysite, preferably kaolinite. The particle size of the calcined pellet is 300 to 850 microns.
[0029] In the adsorption method of the present invention, step (2) is to perform potassium ion exchange on the roasted pellets of step (1) with a soluble potassium salt solution. The concentration of the soluble potassium salt solution is 1.0 to 4.0 mol / L. The soluble potassium salt is at least one of potassium chloride, potassium sulfate, and potassium nitrate, preferably potassium sulfate. The ion exchange in step (2) is performed at a temperature of 50 to 100° C., preferably 60 to 95° C., and for a time of 0.5 to 5 hours, preferably 1 to 3.5 hours.
[0030] In the adsorption method of the present invention, step (3) is to perform ammonium ion exchange on the potassium-type beads after the exchange in step (2) with a soluble ammonium salt solution, wherein the concentration of the soluble ammonium salt solution is 1.0 to 4.5 mol / L. The soluble ammonium salt is at least one of ammonium chloride, ammonium sulfate, and ammonium nitrate. The ion exchange in step (3) is performed at a temperature of 40 to 80° C., preferably 50 to 75° C., and for a time of 0.5 to 7 hours, preferably 1 to 5 hours.
[0031] In the adsorption method of the present invention, the ion exchange in steps (2) and (3) is a kettle exchange or a column exchange, preferably a column exchange. When the ion exchange in step (2) is a kettle exchange, the volume ratio of the soluble potassium salt solution to the potassium-type beads is 5 to 40, preferably 10 to 30; when the ion exchange in step (2) is a column exchange, the volume space velocity of the soluble potassium salt solution is 2 to 25 h -1 , preferably 5 to 20 hours -1 When the ion exchange in step (3) is a kettle exchange, the volume ratio of the soluble ammonium salt solution to the potassium-type beads is 5 to 45, preferably 10 to 35; when the ion exchange in step (3) is a column exchange, the volume space velocity of the soluble ammonium salt solution is 2 to 25 h -1 , preferably 5 to 18 hours -1 .
[0032] In the adsorption method of the present invention, step (4) is to perform lithium ion exchange on the ammonium-type beads after the exchange in step (3) with a soluble lithium salt solution, wherein the concentration of the soluble lithium salt solution is 0.5 to 2.0 mol / L. The soluble lithium salt in step (4) is lithium chloride or lithium hydroxide, preferably lithium hydroxide. The ion exchange in step (4) is performed at a temperature of 30 to 80°C, preferably 40 to 60°C, and the exchange time is 0.5 to 10 hours, preferably 1 to 6 hours; the volume space velocity of the soluble lithium salt solution is 0.5 to 10 h -1 , preferably 2 to 6 hours -1 The exchange is carried out in a two-phase countercurrent column container. Air is introduced into the bottom of the container. The air and the soluble lithium salt solution pass through in countercurrent. The air flow rate is 50-800 L·h -1 , preferably 200 to 600 L·h -1 The soluble lithium salt solution in step (4) can be recycled and reused, and the lithium utilization rate can reach 100%. After the ion exchange in step (4) is completed, the air flow rate is maintained to discharge the liquid in the exchange column, and the discharge rate of the effluent is controlled to be 0.2 to 4 hours. -1 .
[0033] In the adsorption method of the present invention, the in-situ drying in step (4) is carried out in flowing hot air or nitrogen, the drying temperature is 20 to 120° C., preferably 30 to 80° C., and the drying time is 2 to 30 hours, preferably 5 to 24 hours. The in-situ drying is carried out under vacuum conditions, and the vacuum degree (gauge pressure) is -0.02 to -0.08 MPa, preferably -0.04 to -0.08 MPa.
[0034] In the adsorption method of the present invention, the sodium oxide content in the lithium-type X molecular sieve adsorbent is less than 0.5% by mass, the total content of sodium oxide and potassium oxide is less than 0.8% by mass, and the lithium ion exchange degree is greater than 96%.
[0035] The present invention will be further described below by way of examples, but the contents of the present invention are not limited thereto.
[0036] The three important indicators for measuring the performance of adsorbents are oxygen adsorption capacity, nitrogen adsorption capacity and nitrogen-oxygen separation coefficient (nitrogen-oxygen separation coefficient = nitrogen adsorption capacity / oxygen adsorption capacity). The nitrogen and oxygen adsorption capacities are determined using a gas adsorption instrument. When the molecular sieve and the test gas reach adsorption equilibrium, the equilibrium gas adsorption capacity under this pressure is obtained.
[0037] The lithium ion exchange degree of the adsorbent is calculated by the following method: the number of lithium ions per unit mass of the adsorbent / the number of cation exchanges per unit mass of the adsorbent × 100%. Calculation of cation exchange number: The Al2O3 content in the molecular sieve is determined by ICP, and the number of Al atoms is calculated from this, and each aluminum atom corresponds to one cationic charge.
[0038] The lithium utilization of the adsorbent was calculated by the following method: (concentration of lithium ions in the solution before exchange - concentration of lithium ions in the solution after exchange) / concentration of lithium ions in the solution before exchange × 100.
[0039] The sodium oxide content and potassium oxide content in the adsorbent were determined by ICP inductively coupled plasma ion fluorescence spectrometry, and the lithium ion content in the adsorbent was determined by flame photometer.
[0040] The preparation method of NaX molecular sieve in the example of the present invention is as follows:
[0041] Sodium hydroxide, potassium hydroxide, deionized water, low alkalinity sodium aluminate solution (Al2O3 mass fraction of 11.0%, Na2O mass fraction of 15.1%) and water glass are added to a reactor, stirred and mixed to form a molecular sieve synthesis system. The total molar ratio of each material in the molecular sieve synthesis system is: SiO2 / Al2O3=2.40, M2O / SiO2=2.25, H2O / SiO2=45, where M is K and Na, K / (K+Na)=0.23. The above molecular sieve synthesis system is transferred to a reactor, aged at 70°C for 6 hours, hydrothermally crystallized at 95°C for 12 hours, filtered, and the obtained solid is washed with deionized water until the filtrate pH is 8-9, and dried at 80°C for 12 hours to obtain NaX molecular sieve.
[0042] The molar ratio of NaX molecular sieve can be adjusted by adjusting the molar ratio of SiO2 / Al2O3 in the molecular sieve synthesis system.
[0043] Example 1
[0044] (1) 92 kg (basis weight, the same below) of NaX molecular sieve having a SiO2 / Al2O3 molar ratio of 2.00 and 8 kg of kaolinite were uniformly mixed to prepare balls, and the balls having a particle size of 300 to 850 μm were screened and dried at 80° C. for 10 hours and calcined at 540° C. for 4 hours to obtain calcined balls;
[0045] (2) Figure 1 The column ion exchange device shown in the figure uses a 2.0 mol / L potassium chloride solution for exchange at 90°C for 3 hours, and the exchange volume space velocity is 15h -1 , no air is introduced during the exchange, and potassium-type balls are obtained;
[0046] (3) Continue to exchange with 3.0 mol / L ammonium chloride solution at 75°C for 2 hours, with an exchange volume space velocity of 15 h -1 , no air is introduced during the exchange, and ammonium-type pellets are obtained;
[0047] (4) Finally, lithium ion exchange is performed, air is introduced into the bottom of the container, and air and soluble lithium salts pass through in countercurrent. After the exchange is completed, the liquid is drained and dried in situ to obtain lithium-type X molecular sieve adsorbent A. The operating conditions of step (4) and the adsorbent properties are shown in Table 1.
[0048] Example 2
[0049] The lithium type X molecular sieve adsorbent B was prepared according to the method of Example 1, except for the operating conditions of step (4). The operating conditions of step (4) and the adsorbent performance results are shown in Tables 1 and 2.
[0050] Comparative Example 1
[0051] This comparative example illustrates the situation where the NaX molecular sieve is first exchanged for the LiX molecular sieve and then molded with a binder.
[0052] A certain amount of NaX molecular sieve powder with a SiO2 / Al2O3 molar ratio of 2.00 was loaded into Figure 1 In the column ion exchange device shown, ion exchange was carried out under the same conditions as steps (2) to (4) described in Example 1 to obtain LiX molecular sieve, and then formed, dried and calcined under the same conditions as step (1) described in Example 1 to obtain lithium-type X molecular sieve adsorbent DA-1. The operating conditions of lithium exchange and the adsorbent properties are shown in Tables 1 and 2.
[0053] Comparative Example 2
[0054] This comparative example illustrates the case where the NaX molecular sieve is first formed with a binder and then ion exchange is performed, and a kettle exchange method is used in the lithium ion exchange.
[0055] The ammonium-type beads obtained in step (3) of Example 1 were exchanged with a kettle-type lithium hydroxide solution, and then dried outside the kettle at normal pressure. The amount of LiOH solution, the concentration of LiOH solution, the exchange temperature, the exchange time, the drying temperature, and the drying time used in this comparative example were the same as those in Example 1. A lithium-type X molecular sieve adsorbent DA-2 was obtained. The operating conditions of lithium exchange and the adsorbent properties are shown in Tables 1 and 2.
[0056] Example 3
[0057] (1) 85 kg (basis weight, the same below) of NaX molecular sieve having a SiO2 / Al2O3 molar ratio of 2.15 and 15 kg of palygorskite were uniformly mixed to prepare balls, and the balls with a particle size of 300 to 850 μm were screened and dried at 100° C. for 8 hours and calcined at 520° C. for 6 hours to obtain calcined balls;
[0058] (2) Figure 1 In the column ion exchange device shown, 1.25 mol / L potassium sulfate solution was exchanged at 90°C for 1 hour, and the exchange volume space velocity was 20 h -1 , no air is introduced during the exchange, and potassium-type balls are obtained;
[0059] (3) Continue to exchange with 1.5 mol / L ammonium sulfate solution at 70°C for 4 hours, with an exchange volume space velocity of 10 h -1 , no air is introduced during the exchange, and ammonium-type pellets are obtained;
[0060] (4) Finally, lithium ion exchange is performed, air is introduced into the bottom of the container, and air and soluble lithium salts pass through in countercurrent. After the exchange is completed, the liquid is drained and dried in situ to obtain a lithium-type X molecular sieve adsorbent C. The operating conditions of step (4) and the properties of the adsorbent are shown in Tables 1 and 2.
[0061] Example 4
[0062] The lithium type X molecular sieve adsorbent D was prepared according to the method of Example 1, except for the operating conditions of step (4). The operating conditions of step (4) and the properties of the adsorbent are shown in Tables 1 and 2.
[0063] Comparative Example 3
[0064] This comparative example illustrates the situation where the NaX molecular sieve is first exchanged for the LiX molecular sieve and then molded with a binder.
[0065] A certain amount of NaX molecular sieve powder with a SiO2 / Al2O3 molar ratio of 2.15 was loaded into Figure 1In the column ion exchange device shown, ion exchange was carried out under the same conditions as steps (2) to (4) described in Example 3 to obtain LiX molecular sieve, and then formed, dried and calcined under the same conditions as step (1) described in Example 1 to obtain lithium-type X molecular sieve adsorbent DC-1. The operating conditions of lithium exchange and the adsorbent properties are shown in Tables 1 and 2.
[0066] Comparative Example 4
[0067] This comparative example illustrates the case where the NaX molecular sieve is first formed with a binder and then ion exchange is performed, and a kettle exchange method is used in the lithium ion exchange.
[0068] The ammonium-type beads obtained in step (3) of Example 3 were exchanged with a kettle-type lithium hydroxide solution, and then dried outside the kettle at normal pressure. The amount of LiOH solution, the concentration of LiOH solution, the exchange temperature, the exchange time, the drying temperature, and the drying time used in this comparative example were the same as those in Example 3. A lithium-type X molecular sieve adsorbent DC-2 was obtained. The operating conditions of lithium exchange and the adsorbent properties are shown in Tables 1 and 2.
[0069] Example 5
[0070] (1) 90 kg (basis weight, the same below) of NaX molecular sieve having a SiO2 / Al2O3 molar ratio of 2.05 and 10 kg of halloysite were uniformly mixed to prepare balls, and the balls with a particle size of 300 to 850 μm were selected after screening, dried at 110° C. for 4 hours, and calcined at 540° C. for 6 hours to obtain calcined balls;
[0071] (2) Figure 1 The column ion exchange device shown in the figure uses a 1.0 mol / L potassium sulfate solution for exchange at 90°C for 3 hours, and the exchange volume space velocity is 10h -1 , no air is introduced during the exchange, and potassium-type balls are obtained;
[0072] (3) Continue to exchange with 2.5 mol / L ammonium chloride solution at 65°C for 6 hours, with an exchange volume space velocity of 10 h -1 , no air is introduced during the exchange, and ammonium-type pellets are obtained;
[0073] (4) Finally, lithium ion exchange is performed, air is introduced into the bottom of the container, and air and soluble lithium salts pass through in countercurrent. After the exchange is completed, the liquid is drained and dried in situ to obtain lithium-type X molecular sieve adsorbent E. The operating conditions of step (4) and the properties of the adsorbent are shown in Tables 1 and 2.
[0074] Example 6
[0075] The lithium type X molecular sieve adsorbent F was prepared according to the method of Example 5, except for the operating conditions of step (4). The operating conditions of step (4) and the properties of the adsorbent are shown in Tables 1 and 2.
[0076] Comparative Example 5
[0077] This comparative example illustrates the situation where the NaX molecular sieve is first exchanged for the LiX molecular sieve and then molded with a binder.
[0078] A certain amount of NaX molecular sieve powder with a SiO2 / Al2O3 molar ratio of 2.05 was loaded into Figure 1 In the column ion exchange device shown, ion exchange was carried out under the same conditions as steps (2) to (4) described in Example 5 to obtain LiX molecular sieve, and then formed, dried and calcined under the same conditions as step (1) described in Example 5 to obtain lithium-type X molecular sieve adsorbent DE-1. The operating conditions of lithium exchange and the adsorbent properties are shown in Tables 1 and 2.
[0079] Comparative Example 6
[0080] This comparative example illustrates the case where the NaX molecular sieve is first formed with a binder and then ion exchange is performed, and a kettle exchange method is used in the lithium ion exchange.
[0081] The ammonium-type beads obtained in step (3) of Example 5 were exchanged with a kettle-type lithium hydroxide solution, and then dried outside the kettle at normal pressure. The amount of LiOH solution, the concentration of LiOH solution, the exchange temperature, the exchange time, the drying temperature, and the drying time used in this comparative example were the same as those in Example 5. A lithium-type X molecular sieve adsorbent DE-2 was obtained. The operating conditions of lithium exchange and the adsorbent properties are shown in Tables 1 and 2.
[0082] Table 1
[0083]
[0084] Table 2
[0085]
[0086] It can be seen from Table 2 that the adsorbent of the present invention has a larger adsorption capacity than the comparative adsorbent, and when applied to the adsorption method for nitrogen and oxygen separation, its nitrogen and oxygen separation coefficient is higher.
Claims
1. A nitrogen-oxygen separation adsorption method, which uses a lithium-type X molecular sieve adsorbent to separate nitrogen and oxygen from air, characterized in that: The lithium-type X molecular sieve adsorbent is prepared by a method comprising the following steps: (1) NaX molecular sieve and binder are uniformly mixed in a mass ratio of 80-95:5-20, and the mixture is formed into balls by rolling, the balls are dried at 60-110° C., and then calcined at 500-700° C. to obtain calcined balls; (2) subjecting the calcined pellets of step (1) to ion exchange with a soluble potassium salt solution to obtain potassium-type pellets; (3) exchanging the potassium-type beads in step (2) with a soluble ammonium salt solution to obtain ammonium-type beads; (4) exchanging ions of the ammonium beads in step (3) with a soluble lithium salt solution in a two-phase countercurrent exchange manner, draining and in-situ drying are performed in sequence after the exchange is completed to obtain the lithium-type X molecular sieve adsorbent; the two-phase countercurrent exchange is performed in a columnar container, air is introduced into the bottom of the container, and the air and the soluble lithium salt solution pass through in countercurrent.
2. The adsorption method according to claim 1, characterized in that: The SiO2 / Al2O3 molar ratio of the NaX molecular sieve in step (1) is 2.0 to 2.
15.
3. The adsorption method according to claim 1, characterized in that: The binder in step (1) is at least one of palygorskite, kaolinite, dickite, perlite, refractory stone and halloysite.
4. The adsorption method according to claim 1, characterized in that: The particle size of the calcined pellets in step (1) is 300 to 850 microns.
5. The adsorption method according to claim 1, characterized in that: The soluble potassium salt in step (2) is at least one of potassium chloride, potassium sulfate and potassium nitrate.
6. The adsorption method according to claim 1, characterized in that: The ion exchange in steps (2) and (3) is a kettle exchange or a column exchange, preferably a column exchange.
7. The adsorption method according to claim 1, characterized in that: The ion exchange in step (2) is carried out at a temperature of 50 to 100° C., preferably 60 to 95° C., for a time of 0.5 to 5 hours, preferably 1 to 3.5 hours.
8. The adsorption method according to claim 1, characterized in that: The sodium oxide content in the lithium-type X molecular sieve adsorbent is less than 0.5% by mass.
9. The adsorption method according to claim 1, characterized in that: The soluble ammonium salt in step (3) is at least one of ammonium chloride, ammonium sulfate and ammonium nitrate.
10. The adsorption method according to claim 1, characterized in that: The ion exchange in step (3) is carried out at a temperature of 40 to 80° C., preferably 50 to 75° C., for a time of 0.5 to 7 hours, preferably 1 to 5 hours.
11. The adsorption method according to claim 1, characterized in that: The total content of sodium oxide and potassium oxide in the lithium-type X molecular sieve adsorbent is less than 0.8% by mass.
12. The adsorption method according to claim 1, characterized in that: The soluble lithium salt in step (4) is lithium chloride or lithium hydroxide, preferably lithium hydroxide.
13. The adsorption method according to claim 1, characterized in that: The ion exchange in step (4) is carried out at a temperature of 30 to 80°C, preferably 40 to 60°C, for a time of 0.5 to 10 hours, preferably 1 to 6 hours; the volume space velocity of the soluble lithium salt solution is 0.5 to 10 h -1 , preferably 2 to 6 hours -1 .
14. The adsorption method according to claim 1, characterized in that: The air in step (4) has a flow rate of 50 to 800 L·h -1 , preferably 200 to 600 L·h -1 .
15. The adsorption method according to claim 1, characterized in that: The lithium ion exchange degree of the lithium-type X molecular sieve adsorbent is greater than 96%.
16. The adsorption method according to claim 1, characterized in that: The lithium ion solution in step (4) is repeatedly recycled.
17. The adsorption method according to claim 1, characterized in that: After the ion exchange in step (4) is completed, the air flow rate is maintained to discharge the liquid in the exchange column, and the volumetric space velocity of the effluent is controlled to be 0.2 to 4 h. -1 .
18. The adsorption method according to claim 1, characterized in that: The in-situ drying in step (4) is carried out in flowing hot air or nitrogen, the drying temperature is 20 to 120° C., preferably 30 to 80° C., and the drying time is 2 to 30 hours, preferably 5 to 24 hours.
19. The adsorption method according to claim 1, characterized in that: The in-situ drying in step (4) is carried out under vacuum conditions with a vacuum degree of -0.02 to -0.08 MPa, preferably -0.04 to -0.08 MPa.
20. The adsorption method according to claim 6, characterized in that: When the ion exchange in step (2) is a kettle exchange, the volume ratio of the soluble potassium salt solution to the potassium-type beads is 5 to 40, preferably 10 to 30; when the ion exchange in step (2) is a column exchange, the volume space velocity of the soluble potassium salt solution is 2 to 25 h -1 , preferably 5 to 20 hours -1 When the ion exchange in step (3) is a kettle exchange, the volume ratio of the soluble ammonium salt solution to the potassium-type beads is 5 to 45, preferably 10 to 35; when the ion exchange in step (3) is a column exchange, the volume space velocity of the soluble ammonium salt solution is 2 to 25 h -1 , preferably 5 to 18 hours -1 .
21. A method for preparing a lithium-type X molecular sieve adsorbent, characterized in that The preparation method comprises the following steps: (a) mixing NaX molecular sieve and binder in a mass ratio of 80-95:5-20, forming the balls by rolling, drying the balls at 60-110° C., and calcining the balls at 500-700° C. to obtain calcined balls; (b) subjecting the calcined pellets of step (a) to ion exchange with a soluble potassium salt solution to obtain potassium-type pellets; (c) exchanging the potassium-type beads in step (b) with a soluble ammonium salt solution to obtain ammonium-type beads; (d) exchanging ions of the ammonium beads in step (c) with a soluble lithium salt solution in a two-phase countercurrent exchange manner, draining and in-situ drying are performed in sequence after the exchange is completed to obtain the lithium-type X molecular sieve adsorbent; the two-phase countercurrent exchange is performed in a columnar container, air is introduced into the bottom of the container, and the air and the soluble lithium salt solution pass through in countercurrent.
22. The lithium type X molecular sieve adsorbent obtained by the preparation method of claim 21.
Citation Information
Patent Citations
Method for preparing LiLSX molecular screen
CN101289196A
Li-modified X molecular sieve and preparation method thereof
CN102502694A
LiX molecular sieve adsorbent and preparation method thereof
CN102500315A
Synthesis method of interface micro-pore sequence structure LSX (low-silica X-zeolite) molecular sieve for spatially dividing oxygen-enriched adsorbent
CN103055805A
Lithium-based molecular sieve with nitrogen-oxygen separation function as well as preparation method and production equipment of lithium-based molecular sieve
CN113398877A
Cited By
Method for preparing carbon molecular sieve by utilizing biomass waste and application of carbon molecular sieve in realizing C4 olefin and nitrogen-oxygen separation
CN121247794A